Ressignificação do trabalho do coordenador pedagógico no redimensionamento da formação continuada em âmbito escolar - Fabris, Márcia (2018)
Faced with the difficulties that pervade daily teaching work, this study focuses on the re-signification of the work of the pedagogical coordinator, in the sense of resizing the teacher's continuing education. In order to develop research based on epistemological foundations linked to critical Education theorists, an on-site investigation was carried out in an intervention that used action research and participant research as procedures for data collection in continuing education seminars, collectively planned by the participating teachers, with the pedagogical coordinators being the task of organizing and guiding the formative process. Promoting better quality Education in public networks today is a great challenge for the professionals involved in the educational processes. Therefore, pursuing a proposal that may help in the ongoing training of teachers in the school environment, was an attempt to deepen the teaching knowledge to from what constitutes the lived reality, qualifying the professional action in the emancipatory perspective. The intervention process developed was of fundamental importance as verification of the proposal that the theoretical contribution indicated. The meetings brought to the fore anguish that involve the work of the coordinators and some resistance of the teachers in the face of continuing education. However, concepts were deconstructed as the seminars unfolded, the topics listed for study touched on deep-seated beliefs among teachers, promoted debates and tampered with "truths", which are often not questioned at school. It was interesting to note that teachers are not accustomed to expressing their opinions or listening to their colleagues, which has hitherto diverted them from collective work. Also, they distance theory from practice because they consider that theoretical elements do not help solve everyday school problems. It was thus evidenced that the proposed intervention process was essential to initiate a new paradigm in the format of continued formation in this school, where teachers are protagonists and the coordinators responsible for the articulation of the formative process. Thus, creating a reflective environment that leads to the questioning and the consequent constitution of a professional authorship strengthened in the face of daily difficulties was a viable way to help teachers in the development of transformative practices that contribute to the construction of a more humane and fair.